DAMPAK KEPEMIMPINAN, KUALITAS KERJA DAN PROFESIONALISME TERHADAP KINERJA PERSONEL PADA LEMDIKLAT POLRI DI JAKARTA - Setyowati, Retno dwi; Zaharuddin, Zaharuddin (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
Leadership is a person who has skills and strengths, especially superior skills in one area so that he is able to influence other people. Work quality is a result that can be measured by the effectiveness and efficiency of the work carried out. Performance is the work result that can be achieved by a person or group of people in an organization. The aim of the research is as follows: To find out whether leadership and work quality together influence the performance of Polri personnel at the National Police Education and Training Institute in Jakarta. The sampling technique used in this research, the author used the Random Sampling technique or randomly from the existing population of 451 National Police Personnel who were used as samples referring to the Slovin formula in Husein Umar, 2017, obtained a sample of 82 people. The positive influence of leadership on the performance of National Police Personnel obtained a partial value of 0.916, meaning there is a very strong influence or influence with a coefficient of determination of 83.9%. This is proven by hypothesis testing, the value obtained is to = 12.253 > t0.05 (80) = 1.660, so Ho is rejected and Ha is accepted, meaning there is a very significant effect.